2000
DOI: 10.1074/jbc.m006578200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling from E-cadherins to the MAPK Pathway by the Recruitment and Activation of Epidermal Growth Factor Receptors upon Cell-Cell Contact Formation

Abstract: E-cadherins are well characterized cell surface molecules expressed in epithelial cells, which play a major role in cell adhesion through the establishment of calcium-dependent homophilic interactions at sites of cell-cell contacts. They are also integral components of morphogenetic programs controlling the maintenance of the structural and functional integrity of epithelia. Accumulated evidence indicates that the E-cadherinmediated cell adhesion system is highly regulated from inside the cells by a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
273
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(293 citation statements)
references
References 27 publications
17
273
3
Order By: Relevance
“…Several recent studies have shown that cadherins can interact with RTKs at the cell surface and modulate signaling pathways downstream of adherens junctions. For example, E-cadherin has been shown to interact with EGFR and modulate activation of the mitogen-activated protein kinase-ERK pathway, and N-cadherin associates with FGFR-1 to regulate FGFR-1 signaling (Pece and Gutkind, 2000;Suyama et al, 2002;Qian et al, 2004). Our finding is the first to report the activation of an RTK by P-cadherin.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Several recent studies have shown that cadherins can interact with RTKs at the cell surface and modulate signaling pathways downstream of adherens junctions. For example, E-cadherin has been shown to interact with EGFR and modulate activation of the mitogen-activated protein kinase-ERK pathway, and N-cadherin associates with FGFR-1 to regulate FGFR-1 signaling (Pece and Gutkind, 2000;Suyama et al, 2002;Qian et al, 2004). Our finding is the first to report the activation of an RTK by P-cadherin.…”
Section: Discussionmentioning
confidence: 54%
“…Unlike E-and N-cadherin in most cases (Pece and Gutkind, 2000;Suyama et al, 2002;Qian et al, 2004), IGF-1R regulation by P-cadherin is ligand-independent. IGF-1R transactivation has been reported to take place in various systems by both liganddependent and ligand-independent mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…For example, E-cadherin is associated with epidermal growth factor receptor, thus activating the mitogenactivated protein kinase pathway, and N-cadherin has also been found to interact with fibroblast growth factor receptor (Pece and Gutkind, 2000;Suyama et al, 2002;Qian et al, 2004). In this context, we have found that P-cadherin was able to transactivate the insulin-like growth factor-1 receptor in regulation of p120 ctn signaling (our unpublished observations).…”
Section: Discussionmentioning
confidence: 71%
“…E-cadherin is also implicated in regulation of signal transduction through other mediators including Rho family GTPases [43], phosphatidylinositol 3-kinase (PI3K) [44,45], and epidermal growth factor (EGF) receptor [45,46], whereas N-cadherin modulates fibroblast growth factor (FGF) receptor signaling [47] as well as the PI3K/Akt pathway [48,49]. Due to the diverse nature of these dynamic multimolecular interactions, cadherins are properly positioned to functionally integrate cellcell adhesion with regulation of signal transduction pathways and their associated transcriptional programs to control multiple aspects of cell shape and behavior.…”
Section: Phenotypic Plasticity and Cadherin Expression In Eoc A Clasmentioning
confidence: 99%